Size dependence of melting process of armchair hexagonal boron nitride nanoribbon - Nguyen, Hang Thi Thuy; Tran, Van Luong; Ngo, T. Trinh (Communications in Physics, 2024)
The dependence on the initial configuration size of armchair hexagonal boron nitride nanoribbon (h-BNNR) is investigated by molecular dynamics simulation. The initial configuration size of armchair h-BNNR containing 10000, 20000, and 30000 identical atoms of B and N is heated from 50 K to 6000 K via Tersoff potentials to study the dependence on the initial configuration size of the phase transition from crystal to liquid of armchair h-BNNR. Some results can be listed: the phase transition exhibits a first-order type; the phase transition from crystal to liquid states depends on the initial configuration size; the melting points of 10000, 20000, and 30000 atoms are 3640 K, 4000 K, and 4400 K, respectively; the dependence on the heating rate of the armchair h-BNNR is considered for the case of 20000 atoms; in this study range, the melting point decreases as the heating rate decreases; the atomic mechanism of melting process is studied by analyzing the parameter and the appearance of the liquid-like atoms based on the critical value ; the critical value is used to classify solid-like and liquid-like atoms; the appearance of liquid-like atoms upon heating starts from the edges and grow inward; at the phase transition temperature, almost the entire crystal structure of the armchair h-BNNR configuration collapses.